2004
DOI: 10.1111/j.1468-3083.2004.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

HIV seronegative eosinophilic pustular folliculitis successfully treated with doxicycline

Abstract: Eosinophilic pustular folliculitis (EPF) is an unusual disease, first described in adult East Asians in 1970 by Ofuji. It is characterized by follicular papules and pustules tending to coalesce and form plaques involving the trunk, face and extremities. In recent years, it has been often associated with human immunodeficiency virus (HIV) infection or with immunosuppressed and/or oncohaematological patients. EPF has been described in immunocompetent adult caucasian patients only occasionally. The diagnosis requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The results suggest that indomethacin was not effective in 7.7% of patients, highlighting the need for other treatment options for EPF. In previous studies, there have been reported cases of EPF successfully treated with other drugs, including oral cyclosporine, oral antibiotics and topical steroids [8,20,21,22,23]. Table 3 shows the effectiveness of drugs other than oral indomethacin in the present study, and the results suggest that most doctors were less likely to try oral antibiotics and topical steroids in the treatment of EPF.…”
Section: Discussionsupporting
confidence: 45%
“…The results suggest that indomethacin was not effective in 7.7% of patients, highlighting the need for other treatment options for EPF. In previous studies, there have been reported cases of EPF successfully treated with other drugs, including oral cyclosporine, oral antibiotics and topical steroids [8,20,21,22,23]. Table 3 shows the effectiveness of drugs other than oral indomethacin in the present study, and the results suggest that most doctors were less likely to try oral antibiotics and topical steroids in the treatment of EPF.…”
Section: Discussionsupporting
confidence: 45%
“…In particular, we have previously reported that prostaglandin D 2 directly attracts inflammatory cells such as T helper type 2 (Th2) cells and also induces a marked upregulation of eotaxin-3 in sebocytes, which may explain the massive eosinophil infiltration around pilosebaceous units [3]. Other therapeutic options, including nonsteroidal anti-inflammatory drug derivatives, oral and topical corticosteroids, dapsone, cyclosporine, ultraviolet phototherapy, retinoid, antihistamines, antifungals, scabicides and some oral antibiotics, have also been used to treat patients with EPF [1, 2, 4, 5]. Several case reports have revealed that among oral antibiotics, tetracyclines such as minocycline and doxycycline and macrolides such as roxithromycin were effective against EPF [4, 6].…”
mentioning
confidence: 99%
“…Other therapeutic options, including nonsteroidal anti-inflammatory drug derivatives, oral and topical corticosteroids, dapsone, cyclosporine, ultraviolet phototherapy, retinoid, antihistamines, antifungals, scabicides and some oral antibiotics, have also been used to treat patients with EPF [1, 2, 4, 5]. Several case reports have revealed that among oral antibiotics, tetracyclines such as minocycline and doxycycline and macrolides such as roxithromycin were effective against EPF [4, 6]. However, there has been no epidemiological description regarding the use of oral antibiotics in patients with EPF.…”
mentioning
confidence: 99%
“…111,116,[120][121][122] Histopathology of EPF is characterized by an inflammatory infiltrate of lymphocytes and eosinophils in the follicular isthmus. Complete destruction of the follicle rarely occurs.…”
Section: Infancy-associated Variantmentioning
confidence: 99%
“…Furthermore, the effectiveness of certain therapies depends on the clinical variant. 113,116,120,124 The use of topical corticosteroids is usually the first choice treatment for all forms of EPF with a satisfactory response in adults and children. 113 Occasionally, oral corticosteroids may be used.…”
Section: Treatmentmentioning
confidence: 99%